2021
DOI: 10.1097/ajp.0000000000000931
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and Validation of Behavioral Pain Measures and Physiological Pain Measures Factor Structure Extracted From the Pain Assessment Tool Item Scores for Infants Admitted to Neonatal Intensive Care

Abstract: Objective: The objective of the study was to explore and then validate the factor structure of the Pain Assessment Tool (PAT). Materials and Methods:A retrospective medical record review was performed of all infants who were admitted to a neonatal intensive care unit between 2008 and 2018 and had 1 PAT assessment (n = 2111). Scores on items of the PAT were collected. Infants were randomized to either the principal component analysis (n = 1100) to explore the factor structure or confirmatory factor analysis (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The identified studies assess several internationally used, pain assessment instruments including ALPS-Neo ( 3 ), BPSN ( 10 , 11 ),CHIPPS ( 10 ), COMFORT-B/neo ( 1 ), COVERS ( 15 ), EDIN ( 3 )/EDIN6 ( 7 ), NFCS-R ( 10 ), NIAPAS ( 16 ), NIPE ( 17 , 18 ), NIPS ( 4 , 10 ), N-PASS ( 1 , 4 , 10 , 16 ), PAT ( 13 15 ), and PIPP-R ( 2 , 10 , 16 , 19 ). The tools assessed had varying results in correspondence to the eight categories upon which they were evaluated ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The identified studies assess several internationally used, pain assessment instruments including ALPS-Neo ( 3 ), BPSN ( 10 , 11 ),CHIPPS ( 10 ), COMFORT-B/neo ( 1 ), COVERS ( 15 ), EDIN ( 3 )/EDIN6 ( 7 ), NFCS-R ( 10 ), NIAPAS ( 16 ), NIPE ( 17 , 18 ), NIPS ( 4 , 10 ), N-PASS ( 1 , 4 , 10 , 16 ), PAT ( 13 15 ), and PIPP-R ( 2 , 10 , 16 , 19 ). The tools assessed had varying results in correspondence to the eight categories upon which they were evaluated ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…PIPP-R is revised by scoring the contextual factors (gestational age and behavioral state) only if there is a change in behavioral and physiologic factors after the painful event ( 12 ). Researchers found that the PIPP-R was proficient in measuring behavioral and physiological parameters, distinguished distress and pain, and could measure continuous, chronic, and acute pain, but lacked inter-rater reliability and presumed that because low gestational age infants could not express pain, that they did not feel pain ( 13 , 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in unconscious patients, pain assessment depends on the skills of the medical staff, especially nurses, and the type and validity of the instrument. Behavioral Pain Scale, Critical Care Pain Observation Tool (CPOT), and Nonverbal Pain Scale (NVPS) are some of the tools used to assess pain in unconscious patients (10,11).…”
Section: Introductionmentioning
confidence: 99%